GABAergic signaling linked to autophagy enhances host protection against intracellular bacterial infections - Jin Kyung Kim (Nature Portfolio, 2018)
Gamma-aminobutyric acid (GABA) is a major inhibitory neurotransmitter in neuronal systems, but the potential role for such neurotransmitters on the immune system are emerging. Here the authors show GABA signaling is linked to autophagy, enhancing the host response against intracellular bacteria.